Identifying neural circuitry abnormalities in neuropathic pain with transcranial magnetic stimulation and electroencephalogram co-registration - Zhimin Huang; Ying Wang; Yongxing Yan; Ying Liu; Jielin Chen; Huili Liu; Jie Li; Zhongming Gao; Xianwei Che (Neurotherapeutics)
Non-invasive brain stimulation (NIBS) technology such as transcranial magnetic stimulation (TMS) represents a promising treatment for neuropathic pain. However, neural circuitries underlying analgesia remain to be established, which is largely limiting treatment responses. Using TMS and electroencephalogram co-registration (TMS-EEG), this study quantified the circuitry abnormalities in neuropathic pain and their associations with pain symptoms. A group of 21 neuropathic pain individuals and 21 healthy controls were assessed with TMS-EEG delivering to the primary motor cortex (M1). With source modelling, local current density and current propagation were analysed with significant current density (SCD) and scattering (SCS) respectively. The SCS and SCD data converged on higher activities in neuropathic pain individuals than healthy controls, within the emotional affective (perigenual anterior cingulate cortex, pgACC), sensory nociceptive (primary somatosensory cortex, S1), and the attentional cognitive (anterior insula, aINS; supracallosal anterior cingulate cortex, scACC) structures of pain. Moreover, current propagation to the pgACC was associated with lower pain-related negative emotions, while current propagation to the aINS with higher pain-related negative emotions. Using concurrent TMS-EEG, our data identified abnormal pain circuitries that could be utilised to improve treatment efficacy with brain stimulation technologies.